Previsão para o desempenho ótimo de um duplo-tubo aletado para a transferência de um calor em regime laminar - Colle, Sérgio (1976)
Theoretical study of the steady-state laminar flow and steady-state heat transfer in finned double-tube heat exchangers. Here, the fins are plane, straigh and continuous and equally spaced, fixed on the external surface of the inner tube. Two boundary conditions are discussed; in the first one, a constant and uniform heat flux is assumed to apply steadily over the inner tube surface and over each fin; in the second one, a constant peripheral temperature distribution is assumed to apply over the inner tube surface and each fin, while a constant and uniform heat flux is assumed in the longitudinal direction of the tube and the fins. For each case, a constant and uniform heat flux is assumed on the outer tube surface. The related boundary value problems are solved analitically, with the aid of complete Green's functions and the inverse method. The influence of the geometry on the velocity and temperature distribution is analized in detail. In order to discuss and analize the finned double-tube performance as a compact heat exchanger, appropriate Nusselt numbers are defined. The predictions of the global and optimum performance are made by means of the Nusselt number curves i.e., the relationship etween the Nusselt number, the boundary conditions and the geometric characteristics of the duct. Very, litle has been published on this subject in the related literature. However, some limiting cases of the present study could be compared and are in good agreement with the available data.